Antioxidant and Anti-Hyaluronidase Activities of Dragon Fruit Peel Extract and Kaempferol-3-O-Rutinoside - Liana, Liana; Rizal, Rizal; Widowati, Wahyu; Fioni, Fioni; Akbar, Khainir; Fachrial, Edy; Lister, I Nyoman Ehrich (Fakultas Kedokteran Universitas Brawijaya, 2019)
Aging is a natural process in human life and is triggered by the presence of free radicals (ROS). The use of antioxidants from natural ingredients is one of the breakthroughs to overcome aging and counteract the harmful effects caused by the free radicals. This study aimed to determine and compare the antioxidant activity of H2O2 scavenging and hyaluronidase inhibition of red dragon fruit peel extract (DFPE) and kaempferol-3-o-rutinoside (KOR) compounds. Dragon fruit peel extract (DFPE) is obtained through extraction by maceration method using 70% ethanol solvent. The design of this study included antioxidant and anti-aging activity assay of EKBN and KOR at the series concentration of 15.63; 31.25; 62.50; 125; 250; 500 µg/mL through H2O2 scavenging, as well as the DFPE and KOR hyaluronidase inhibition assay at the series concentration of 5.21; 10.42; 20.83; 41.7; 83.33; 166.67 µg/mL. EKBN shows that the average activity of H2O2 scavenging is lower than KOR. In addition, the IC50 values of KOR for H2O2 scavenging is lower (351.46±2.30ug/mL) than DFPE (409.64±23.17ug/mL). While, KOR also has higher values of inhibitory activity than of the DFPE. However, the IC50 value of KOR for hyaluronidase inhibition activity was 84.07±10.46µg/mL, equivalent to the IC50 value of DFPE (85.32±10.24µg/mL). The presence of antioxidant and anti-aging activity in the EKBN is probably caused by betalain and the KOR compound itself contained in red dragon fruit. The results of the paired-samples T-test on antioxidant activity and anti-aging of DFPE and KOR showed non-significant difference. Thus, DFPE has an equivalent antioxidant and anti-aging through H2O2 scavenging and hyaluronidase activity as possessed by the KOR compound.